Next generation ice core technology reveals true minimum natural levels of lead (Pb) in the atmosphere: insights from the Black Death - More, Alexander F.; Spaulding, Nicole E.; Bohleber, Pascal; Handley, Michael J.; Hoffmann, Helene; Korotkikh, Elena V.; Kurbatov, Andrei V.; Loveluck, Christopher P.; Sneed, Sharon B.; McCormick, Michael; Mayewski, Paul A. (AGU Publications, 2017)
Current policies to reduce lead pollution in the air are based on the assumption that pre-industrial levels of lead in the air were negligible, safe or non-existent. This trans-disciplinary article shows that this is not the case, using ‘next-generation’ laser technology in climate science, in combination with detailed historical and archaeological records in as many as 7 languages, from all over Europe.